Technical Guidance On Groundwater Identification To Overcome Drought In Tanamerah Village, Saronggi, Sumenep, East Java. - Gautama, Gregorius Aryoko; Jayaputra, Harsalim Aimunandar; Aditya, Muhammad Tri; Novianto, Dandung; Rahardjo, Bobby Asukmajaya; Pungarto, Irwanda Yuni (West Science Interdisciplinary Studies, 2025)
Tanamerah Village is one of fourteen villages in Saronggi District, Sumenep Regency, East Java. Villagers experience water difficulties during both the rainy season and the dry season. Technical guidance will be carried out for groundwater identification to find out where the groundwater points are located that are able to meet the community's water needs. The method used for identification makes six tracks with varying distances between tracks. The length of each passage is twelve meters, and the depth of each passage is three hundred meters. Identification was carried out on village treasury land with an area of 500 m2. Six tracks in this service, the distance between tracks is 5-8 m, and the length of each track is 12 m. Track 1 was obtained from groundwater at a depth of 80m, and track 2 was obtained from groundwater at a depth of 80 m. Track 3 was obtained from groundwater at a depth of 70 m, and track 4 was obtained from groundwater at a depth of 20 m. Passage 5 is obtained from groundwater at a depth of 20 m, and passage 6 is obtained from groundwater at a depth of 70 m. Recommended drilling point is located on the TM1 line at point 8 with a depth of 80 m.